The Dalton quantum chemistry program system. (23rd September 2013) - Aidas, Kestutis; Angeli, Celestino; Bak, Keld L.; Bakken, Vebjørn; Bast, Radovan; Boman, Linus; Christiansen, Ove; Cimiraglia, Renzo; Coriani, Sonia; Dahle, Pål; Dalskov, Erik K.; Ekström, Ulf; et al.
Abstract : Abstract : Dalton is a powerful general‐purpose program system for the study of molecular electronic structure at the Hartree–Fock, Kohn–Sham, multiconfigurational self‐consistent‐field, Møller–Plesset, configuration‐interaction, and coupled‐cluster levels of theory. Apart from the total energy, a wide variety of molecular properties may be calculated using these electronic‐structure models. Molecular gradients and Hessians are available for geometry optimizations, molecular dynamics, and vibrational studies, whereas magnetic resonance and optical activity can be studied in a gauge‐origin‐invariant manner. Frequency‐dependent molecular properties can be calculated using linear, quadratic, and cubic response theory. A large number of singlet and triplet perturbation operators are available for the study of one‐, two‐, and three‐photon processes. Environmental effects may be included using various dielectric‐medium and quantum‐mechanics/molecular‐mechanics models. Large molecules may be studied using linear‐scaling and massively parallel algorithms. Dalton is distributed at no cost fromhttp://www.daltonprogram.org for a number of UNIX platforms. This article is categorized under: Software > Quantum Chemistry